Imaging of Acute Cervical Spine Trauma: When to Obtain Which Modality - Ulbrich, Erika J.; Carrino, John A.; Sturzenegger, Matthias; Farshad, Mazda (Seminars in Musculoskeletal Radiology, 2013)
The current knowledge and evidence around the merits of different imaging modalities for the evaluation of cervical spine injuries are reviewed. The National Emergency X-Radiography Use Study, Canadian Cervical Spine rule, and American College of Radiology appropriateness criteria are reviewed and summarized. The advantages and disadvantages of available imaging modalities for selected cervical spine injury patterns are also illuminated to simplify the decision making on when to use which modality.
Keywords: cervical spine trauma; nexus; CCR; imaging modalities; ACR appropriateness criteria